Synthesis and Antioxidant Activity of Substituted Phenylalkene Hydroxamic Acids - D. WAGH, RAJENDRA; MAHAJAN, H.S.; KASKHEDIKAR, S.G. (Asian Journal of Chemistry, 2010)
A series of phenylalkene hydroxamic acids ahve been synthesized by acylation of hydroxylamine with substituted acyl chlorides of the substituted cinnamic acids. The substituted cinnamic acids were prepared from substituted benzaldehydes by emphasizing knoevengel reaction. The title compounds were screened for antioxidant activity, in vitro. Compounds A7, A10, A11 exhibited most significant activity activities amongst all the evaluated compounds. Compound A10 showed lowest IC50 value (8.668 mM) ad A5 showed highest IC50 value (954.734 mM).